Effect of shot-peening on corrosion behavior of austenitic steel in supercritical carbon dioxide at 700 °C. (1st May 2022) - Gui, Yong; Zhao, Qinxin; Wang, Shuo; Liang, Zhiyuan
Abstract: The contribution of shot-peening treatment on the corrosion resistance of Sanicro 25 exposed to supercritical carbon dioxide (S-CO2 ) at 700 °C and 15 MPa was investigated. Complex corrosion layers formed on shot-peened Sanicro 25 were approximately ten times thicker than those formed on non-peened Sanicro 25. Rapid diffusion paths induced by shot-peening treatment accelerated inward diffusion of C, resulting in the formation of subsurface carbide-containing core/shell structure precipitates. Increased voids in shot-peened Sanicro 25 and the stress concentration promoted scale spallation after exposure. In summary, shot-peened Sanicro 25 exhibited worse corrosion resistance compared to non-peened Sanicro 25 in 1000 h. Highlights: The contribution of shot-peening treatment on the corrosion resistance of Sanicro 25 exposed to supercritical carbon dioxide at 700 °C and 15 MPa was investigated. Complex corrosion layers formed on shot-peened Sanicro 25 were approximately ten times thicker than those formed on non-peened Sanicro 25. Increased voids in shot-peened Sanicro 25 and the stress concentration promoted scale spallation after high-temperature S-CO2 exposure. Shot-peened Sanicro 25 exhibited worse corrosion resistance compared to non-peened Sanicro 25 in 1000 h.